Minimizing Technical Failure of Percutaneous Balloon Compression for Trigeminal Neuralgia Using Neuronavigation. (9th March 2014) - Georgiopoulos, Miltiadis; Ellul, John; Chroni, Elisabeth; Constantoyannis, Constantine
Abstract : Objective . Percutaneous balloon compression (PBC) is an effective and safe management for medically refractory trigeminal neuralgia; however, technical failure to cannulate the foramen ovale (FO) using only fluoroscopy is a significant problem in some cases. In this paper, we suggest the use of intraoperative navigation, in cases of reoperation due to prior technical failure to cannulate the FO under fluoroscopy. Methods . A total of 174 patients underwent PBC for TN since 2003. In 9 cases the penetration of the FO was not accomplished. Five of those patients were reoperated on for PBC using navigation from March 2012 to September 2012. Surgical technique: preoperatively, a head Computed Tomography (CT) scan is performed and the acquired images are imported into the navigation system. Intraoperatively, a small reference frame is strapped firmly to the patient's forehead, the CT images are registered, and cannulation is performed under the guidance of the navigation system. Results . In all patients, the operation overall was completed successfully. Moreover, all patients reported complete pain relief immediately postoperatively and no complications were recorded overall. Conclusions . We suggest the use of neuronavigation in cases of technical failure of PBC. That technique involves technology with significant advantages helping the successful cannulation of the FO and seems more efficient and safer.